Public eTendering in Portugal: vortalGOV® case study - Sobral, Miguel (2010)
Vortal is the leader in electronic platform operations for public and private market contracting in Portugal and one of four international reference points in electronic public contracting. In 2004, after having achieved a wealth of private market experience acquired through electronic market operations within the construction sector through its brand Econstroi, Vortal launched a new brand, vortalGOV, which is specifically aimed a the public sector and indeed the first ever electronic public tender in Portugal was launched through this Vortal platform. In 2008 a new public contract law came into force directing all entities linked to electronic contracting platform use to formalise pre-contracting. Furthermore, that same law specified that platforms should not charge the economical operators, the suppliers, any fees to access their basic services. In other words, revenues from the Public eTendering platforms should only come from public entities awarding the contracts. In 2009, order to meet these new legal requirements, Vortal launched its free Universal service. In 2010, Vortal decided to contract the services of a specialist company to carry out a satisfaction survey of its Universal clients. The Vortal Board of Directors sought to evaluate possible scenarios for the development of the public sector market drawing on the experience the company had acquired in the private market. The vortalGOV case study aims to stimulate reflection on the innovation surrounding the legal limitations of business operations, based on an analysis of customer value.